Frequent expression of CD30 in extranodal NK/T‐cell lymphoma: Potential therapeutic target for anti‐CD30 antibody‐based therapy. Issue 1 (20th October 2017) - Kawamoto, Keisuke; Miyoshi, Hiroaki; Suzuki, Takaharu; Sasaki, Yuya; Yamada, Kyohei; Yanagida, Eriko; Muto, Reiji; Kiryu, Maiko; Sone, Hirohito; Seto, Masao; Ohshima, Koichi; Takizawa, Jun
Abstract: Extranodal NK/T‐cell lymphoma, nasal type (ENKTL) is a subtype of non‐Hodgkin lymphoma with a poor prognosis. Although first‐line treatments for patients with localized ENKTL have been established, there is no gold standard treatment for patients with advanced ENKTL and refractory and/or relapsed disease. Anti‐CD30 antibody‐based therapy, including brentuximab vedotin (BV), has been shown to target malignant lymphomas with CD30 expression. In particular, this therapeutic agent has recently been suggested to be effective for Hodgkin lymphoma and mature T‐cell lymphoma. However, the efficacy of BV toward ENKTL has not yet been established. Therefore, we investigated the expression of CD30 in a large cohort to evaluate BV as a potential treatment for ENKTL. In this study, 97 Japanese patients with newly diagnosed ENKTL between January 2007 and December 2015 were enrolled. Flow cytometry and immunohistochemistry were performed for the evaluation of CD30 expression. If the cut‐off value of CD30 expression is 1% or more, there were 55 positive cases (56.5%). According to the localization of lesion, the frequency of CD30 expression was significantly higher in the non‐nasal type than in the nasal type ( P  = .0394). No differences were observed in almost all clinical characteristics between CD30‐positive cases and CD30‐negative cases. In addition, the expression of CD30 was not a prognostic factor for either overall survival or progression‐free survival. In conclusion, frequent expression of CD30 in ENKTL suggests anti‐CD30 antibody‐based therapy may be an effective treatment.